Konsep Punishment Perspektif Ibnu Sahnun (analisis kitab Adab al Muallimin) - Chusnul Muali; Helmiyatus Sa’adah (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2018)
This study analyzes how the concept of punishment is in the learning process. Given how much controversy caused by the application of penalties that are considered not ideal and as acts of violence. Therefore, the concept of punishment is needed to improve the application of penalties that are not in accordance with the provisions of the Law and Islamic Shari'a. This literature study examines the concept of applying the perspective penalty of Ibnu Sahnun, which places more emphasis on the state of child psychology. With the hope that the concept of educational punishment becomes a reference in the process of applying punishment in the learning process. The main source of this study is a book by Ibnu Sahnun which deals with punishment, namely the book Adab al muallimin, also a book written by other writers who support the application of punishment in education. This study concludes that there are three types of educative punishment by Ibnu Sahnun, namely bi nadri (see with a cynical view), bi oral (advise), bi darban (punch). The three types of punishment are very relevant when applied in the learning process